Weight loss program outcome of obese attending AL-Kindy obesity research and therapy unit - Khazaal, Faris A. K.; Leibi, Abdul Hadi; Jasim, Insaf; alhergani, Zidan (AL-Kindy College Medical Journal, 2015)
Background: overweight and obesity are the fifth leadingrisk for global deaths. At least 2.8 million adults die eachyear as a result of being overweight or obese. Numerousstudies show that weight loss, even if only 5-10%,significantly improves dyslipidemia, hypertension, diabetesmellitus, risk for osteoarthritis and its symptoms and risk forselected cancers.Objectives: is to evaluate the effect of diet and exerciseprogram on anthropometric and biochemical status of adultobese patients.Methods: descriptive study. 124 adult obese patientsattending Al Kindy obesity research and therapy unit duringDecember 2012 were included. Measurement of Wt, heightHt and WC performed and BMI was calculated. Laboratorytest analysis, on the fasting state, was performed for plasmaglucose, uric acid, Ch, Tg, and HDL, and LDL and VLDLlevels were estimated. Patients were advised aboutdecreasing their weight by decreasing calories intake byabout 500 calories daily with increasing physical activity toone hour of medium tension aerobic exercise for 3 monthsthen reexamined.Results: eighteen point five percents are males and 81.5% are females with mean age of 37.3 years, weight was reduced by 3 kilograms and waist by 6.6 cm and BMI by 1.9Kg/m2 within 3 months. Age groups, 30-39 and 40-49 yearsshowed better response (3.5-4 kg Wt loss), while males lost2.6 kg and female lost 3.8 kg within 3 months. Withreduction of total cholesterol by 17.3 mg/dl and reduction oftotal triglycerides by 24 mg/dl and reduction of LDL by 5mg/dl and of VLDL by 4.3 mg/dl and increment of HDL by1.8 mg/dl. Mean fasting plasma glucose fell by 6.3 mg/dland the uric acid level by 0.13 mg/dl.Conclusions: mean weight loss of this program was modest and middle age group responded to weight loss program better than young significantly, old and males respond less than females but insignificantly. In addition weight loss significantly resulted in correction of lipoproteins, blood glucose, and urate levels.